1999
DOI: 10.1074/jbc.274.18.12376
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Neutrophil Cell Surface Glycosaminoglycan That Mediates Binding of Platelet Factor 4

Abstract: Platelet factor 4 (PF-4) is a platelet-derived

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 42 publications
4
88
0
Order By: Relevance
“…Our laboratory has also reported the many biological activities of the chemically fully sulfated poly-and oligosaccharides (Chaidedgumjorn et al, 2002;Suzuki et al, 2001;Toida et al, 1999Toida et al, , 2000. Chondroitin sulfate has been found in many tissues (Suzuki et al, 1968) and cells (Ohhashi et al, 1984;Petersen et al, 1999;Stevens et al, 1988), and has been reported to interact with various biologically important molecules and regulate their functions. We have demonstrated the importance of the content, position, and number of O-sulfo groups in CS for immunological activity of the OVA-stimulated murine splenocytes in vitro (Akiyama et al, 2004;Sakai et al, 2002a).…”
Section: A New Concept For Explaining the Effect Of Chondroitin Sumentioning
confidence: 88%
“…Our laboratory has also reported the many biological activities of the chemically fully sulfated poly-and oligosaccharides (Chaidedgumjorn et al, 2002;Suzuki et al, 2001;Toida et al, 1999Toida et al, , 2000. Chondroitin sulfate has been found in many tissues (Suzuki et al, 1968) and cells (Ohhashi et al, 1984;Petersen et al, 1999;Stevens et al, 1988), and has been reported to interact with various biologically important molecules and regulate their functions. We have demonstrated the importance of the content, position, and number of O-sulfo groups in CS for immunological activity of the OVA-stimulated murine splenocytes in vitro (Akiyama et al, 2004;Sakai et al, 2002a).…”
Section: A New Concept For Explaining the Effect Of Chondroitin Sumentioning
confidence: 88%
“…However, this molecule was expressed neither on monocytes nor on neutrophils. We have shown previously that on human neutrophils a chondroitin sulfate proteoglycan specifically binds PF-4 and is involved in cell activation (14,42), indicating that there may exist more than one receptor for the chemokine. The hypothesis of PF-4-binding to such a type of receptor is supported by our unpublished observation that heparin completely abolished PF-4-induced monocyte oxidative burst.…”
Section: Discussionmentioning
confidence: 99%
“…A little yet appreciable amount of the disaccharide unit ⌬HexA-GalNAc(4,6-O-disulfate) typical for CS-E was found, representing 2-3% of the total CS disaccharides as shown in Table IV. Recently it has been demonstrated that CS-E binds to various types of collagen to different degrees (24) and platelet factor 4 (27). CS-E is expressed in a cell-type-and tissue-type-specific manner and in a developmentally regulated fashion (reviewed in Ref.…”
Section: Effects Of Various Gags On the Formation Of The Collagenindumentioning
confidence: 99%